2018
DOI: 10.2147/idr.s150431
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect evaluation of moxalactam against extended-spectrum &beta;-lactamase-producing <em>Escherichia coli</em> and <em>Klebsiella pneumoniae </em>with in vitro pharmacokinetics/pharmacodynamics simulation

Abstract: ObjectivesThe aim of this study was to evaluate the bactericidal effects of moxalactam (MOX), cefotaxime (CTX), and cefoperazone/sulbactam (CFZ/SBT) against extended-spectrum β-lactamase (ESBL) producing Escherichia coli and Klebsiella pneumoniae, using an in vitro pharmacokinetics (PK)/pharmacodynamics model.MethodsTwo clinical ESBL-producing strains (blaCTX-M-15 positive E. coli 3376 and blaCTX-M-14 positive K. pneumoniae 2689) and E. coli American Type Culture Collection (ATCC)25922 were used in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Against isolates with high MICs (4, 8, and 16 mg/L), MCS of CFZ/SBT simulated regimens failed to reach 90% PTA. Moreover, our previous in vitro PK/PD study demonstrated that regimens of CFZ/SBT (2 g iv q8h) against ESBL producers with high MICs failed to maintain effective killing, and allowed significant regrowth 37. FEP was relatively stable against ESBL compared with third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 98%
“…Against isolates with high MICs (4, 8, and 16 mg/L), MCS of CFZ/SBT simulated regimens failed to reach 90% PTA. Moreover, our previous in vitro PK/PD study demonstrated that regimens of CFZ/SBT (2 g iv q8h) against ESBL producers with high MICs failed to maintain effective killing, and allowed significant regrowth 37. FEP was relatively stable against ESBL compared with third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 98%
“…The analysis ( Figure 1 ) revealed that conclusions drawn earlier 1 , 2 on the basis of a study on a few strains may not be valid. My analysis revealed that of the 3,242 bacteria tested in our laboratory, using Clinical and Laboratory Standards Institute 3 guidelines, 50.6% were identified as ESBL producers.…”
mentioning
confidence: 85%
“…In a recently published article 1 moxalactam has been claimed to be very effective on extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae , concluding “MOX demonstrated excellent bactericidal effect, which is worthy of further exploration to serve as an alternative therapeutic agent against ESBL-producing Enterobacteriaceae”. Similar claims have also been made earlier.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Thus, the prudent use of antimicrobials is as crucial as finding alternatives of carbapenems to treat the infections caused by ESBLproducing isolates and avoid exacerbation of the spreading of ESBLs. 4 When detecting ESBL-positive strains, microbiology laboratories should provide the clinician with reliable therapeutic options for successfully treating infected patients, since ESBL-distribution has been shown to differ among countries. 5 Inadequate surveillance practices and inefficient regulatory system play a key role in the determination of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%